MENAKAR MINAT PELAKU USAHA MIKRO KECIL MENENGAH PADA PENGGUNAAN PRODUK TEKNOLOGI FINANSIAL - Purba, Mortigor Afrizal (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2023)
This research was conducted to find out how much the level of financial literacy of micro, small and medium enterprises and to find out whether or not there was an influence of financial literacy and promotion strategies through social media on the interest in using technology financial products. This research is a quantitative descriptive study using probability random sampling techniques with respondents of micro, small and medium enterprises. Data collection used a questionnaire method with a likert scale model and distributed to 100 respondents. The data used are descriptive, simple, and multiple regression analysis using SPSS 22.0. The results of this study indicate that (1) financial literacy of the micro, small and medium enterprises is included in the category of sufficient literate, quite a category with a percentage of 81.12% (2) There is a positive and significant influence between financial literacy and interest in using financial technology products. (3) There is a positive and significant influence between the promotion strategy variables through social media on the interest in using financial technology products. (4)There is a positive and significant influence on the variable level of financial literacy and promotion strategies through social media on the interest in using financial technology products. This illustrates that micro, small and medium enterprises to use financial technology products falls into the very satisfying category.